1978
DOI: 10.1044/jshr.2103.421
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Two Types of Motor Practice on Stuttering Adaptation

Abstract: The present study identifies and compares the effects of two types of motor practice on stuttering adaptation. The study was designed to determine if whispered reading practice affects stuttering adaptation, and if practice in reading aloud is superior to whispered reading in promoting adaptation. In a control condition, eight stutterers read one of two matched passages aloud five times in succession. In an experimental condition, the remaining passage was read aloud on the first and fifth trials, and was read… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1982
1982
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…Johnson and Rosen (1937) originally reported about an 84% reduction in words stuttered during whispered oral reading. This finding was essentially replicated in a more recent study by Rami, Kalinowski, Rastatter, Holbert and Allen (2005), although there are also reports of lesser reductions (Bruce & Adams, 1978; Perkins, Rudas, Johnson & Bell, 1976). Whispering has also been described as requiring an increase in the speaker’s level of vocal effort (Monoson & Zemlin, 1984), as compared with normal speech, presumably because of the unusual circumstance of producing articulatory movements but without phonation.…”
Section: Speech Effort and Fluency-inducing Conditionssupporting
confidence: 58%
“…Johnson and Rosen (1937) originally reported about an 84% reduction in words stuttered during whispered oral reading. This finding was essentially replicated in a more recent study by Rami, Kalinowski, Rastatter, Holbert and Allen (2005), although there are also reports of lesser reductions (Bruce & Adams, 1978; Perkins, Rudas, Johnson & Bell, 1976). Whispering has also been described as requiring an increase in the speaker’s level of vocal effort (Monoson & Zemlin, 1984), as compared with normal speech, presumably because of the unusual circumstance of producing articulatory movements but without phonation.…”
Section: Speech Effort and Fluency-inducing Conditionssupporting
confidence: 58%
“…Research into the role of the larynx in stuttering declined after the 1980s when studies suggested that (i) stuttering is reduced but not eliminated when speaking in the absence of phonation, as in whispering (Perkins et al ., ; Bruce & Adams, ), (ii) paralysing the larynx by injecting botulinum toxin yields only a short‐term reduction in stuttering (Ludlow, ; Brin et al ., ), although the timeframe is typical of botulinum toxin treatments of neuromuscular disorders (Blitzer & Sulica, ), and (iii) stuttering may still occur when the larynx is excised (Tuck, ; although see Wingate, ). Interestingly, larynx excision among PWNS can result in adult‐onset stuttering (Freeman & Rosenfield, ; Rosenfield & Freeman, ).…”
Section: Discussionmentioning
confidence: 99%
“…Oral practice may also allow the subject to regain control of temporal patterning necessary to gain motor control over speaking. Bruce and Adams (1978) also examined the concept of adaptation. In this particular study, the researchers examine the effects of whispered rehearsal on adaptation.…”
Section: Studies Of Adaptationmentioning
confidence: 99%
“…These researchers have attempted to clarify what exactly allows for adaptation to occur in some speakers (Besozzi & Adams, 1969, Bruce and Adams, 1978, Prins & Hubbard,1990, and Prins & Hubbard 1992. Since changes in fluency primarily occurred in situations where readings were performed orally, it would appear that modifications in physiologic and acoustic aspects of speech may be contributing•factors.…”
Section: Studies Of Adaptationmentioning
confidence: 99%